Medical tourism destination image and its relationship with the intention to revisit: a study of Chinese medical tourists in Malaysia - Cham, Tat-Huei; Lim, Yet-Mee; Sia, Bee-Chuan; Cheah, Jun Hwa; Ting, Hiram (Routledge, 2020)
Medical tourism in Malaysia has grown over the years and has become a promising industry. However, due to the establishment of China’s Belt and Road Initiative (BRI), we see a spill-over effect where more Chinese people visit and seek medical treatments in Malaysia. Attracting these Chinese medical tourists has become a great competition as Malaysia is not the sole player in the South East Asia region. The objective of this study is to examine the factors influencing Malaysia as a medical tourism destination among Chinese medical tourists. Self-administered questionnaires were used to collect data from a sample of 600 respondents to test the hypothesized relationships. The data were analyzed using a structural equation modeling approach via AMOS and SPSS. The results show that country-specific factors (country knowledge, safety and security, accessibility, and price reasonableness) and social factors (word-of-mouth and social media) are significant predictors of the image of Malaysia as a medical tourism destination, which in turn, affect perceived value and intention to revisit. This study is one of the few that examines the perception of Chinese medical tourists, a lucrative market that contributes significantly to the global medical tourism industry. Theoretical and managerial implications of the research are discussed.